The Mechanism of an Fe-Based MOF Material as a Foliar Inhibitor and Its Co-Mitigation Effects on Arsenic and Cadmium Accumulation in Rice Grains - Tianyu Wang; Hao Cui; Weijie Li; Zhenmao Jiang; Lei Li; Lidan Lei; Shiqiang Wei (Agronomy, 2025)
Arsenic (As) and cadmium (Cd) in rice grains are major global food safety concerns. Iron (Fe) can help reduce both, but current Fe treatments suffer from poor stability, low leaf absorption, and fast soil immobilization, with unclear underlying mechanisms. To address these issues, an Fe-based metal–organic framework (MIL-88) was modified with sodium alginate (SA) to form MIL-88@SA. Its stability as a foliar inhibitor and its leaf absorption were tested, and its effects on As and Cd accumulation in rice were compared with those of soluble Fe (FeCl3) and chelating Fe (HA + FeCl3) in a field study on As–Cd co-contaminated rice paddies. Compared with the control, MIL-88@SA outperformed or matched the other Fe treatments. A single foliar spray during the tillering stage increased the rice yield by 19% and reduced the inorganic As and Cd content in the grains by 22.8% and 67.8%, respectively, while the other Fe treatments required two sprays. Its superior performance was attributed to better leaf affinity and thermal stability. Laser ablation inductively coupled plasma–mass spectrometry (LA–ICP–MS) and confocal laser scanning microscopy (CLSM) analyses revealed that Fe improved photosynthesis and alleviated As–Cd stress in leaves, MIL-88@SA promoted As and Cd redistribution, and Fe–Cd co-accumulation in leaf veins enhanced Cd retention in leaves.